Vitronectin promotes proliferation and metastasis of cervical cancer cells via the epithelial-mesenchymal transition - Lin, Yao; Bian, Lihong; Zhu, Guangwei; Zhang, Bin (Frontiers in Oncology, 2024)
BackgroundVitronectin (VTN) is a multifunctional glycoprotein in blood and the extracellular, which could be an effective biomarker for many cancers. However, its role in cervical cancer is under investigated. In this study, we aimed to determine the molecular function of VTN and its potential mechanism in cervical cancer (CC).Materials and methodsUp- and down-regulated VTN expression was determined in Hela and C33A cells. Reverse transcription, qRT-PCR, and Western blotting test were performed to identify VTN mRNA and protein levels, separately. CCK-8 assay and colony formation assay were carried out to evaluate proliferation abilities of CC cells. A scratch test and a transwell chamber assay were performed to determine cell migration and invasion ability. Expression levels of epithelial-mesenchymal transition (EMT)-related proteins were measured by Western blotting.ResultsCell models with up- and down-regulated VTN expression in Hela and C33A cells were successfully established, as confirmed by Western blotting and qPCR. CCK-8 and colony formation assays demonstrated that VTN overexpression significantly enhanced the proliferation of both Hela and C33A cells. Wound healing and Transwell migration assays further indicated that VTN overexpression markedly promoted the migratory and invasive capabilities of these cells. Moreover, Western blotting analysis revealed that VTN overexpression led to a decrease in ZO-1 and E-cadherin protein levels and an increase in β-catenin and N-cadherin levels, whereas VTN knockdown yielded the opposite effect. These findings suggest that VTN promotes cervical cancer cell malignancy through epithelial-mesenchymal transition (EMT).ConclusionVTN plays a tumor-promoting role in CC by promoting the EMT of cervical cancer cells.